Changes in nitrogen fractions and proteolytic activities in the cotyledons of germinating lentils (Revista Española de Fisiología, 1983)
Changes in ninhydrin positive material, free amino acids and protein content during germination of seeds of Lens culinaris Med.have been studied.Ninhydrin positive material and free amino acids reached their highest concentration at the fifth day of germination.Total protein which represents 21% of the total dry weight of the lentil cotyledons, suffers a degradation of only 24% in seven days of germination; in the same period of time, reserve proteins underwent a degradation of 69%, legumin being the more abundant at the start, and the more rapidly depleted.Five different classes of proteolytic activities have been reported in lentil cotyledons: caseinolytic, active against the reserve proteins of the lentil cotyledons themselves, aminopeptidase, peptidehydrolase, carboxypeptidase and dipeptidase.The removal of the axis did not seem to exert any significant influence on the enzymatic activity.